Problem Based Learning in Mathematics - Letchumanan, Malathi (Institute for Mathematical Research, 2009)
Research shows that the introduction of problem based learning (PBL) could foster student-centered learning, enhances students' abilities in learning, change their perception towards the subject matter and creates active learners.Although this approach has been applied in other disciplines, there is still lack of research focusing on the adoption of PBL approach in the Mathematics curriculum in countries such as Malaysia. Thus, this paper examines and summarizes some of the research conducted in the area of PBL in teaching and learning Mathematics and its effectiveness from students' perspective. The review shows PBL adoption in Mathematics is gaining positive feedbacks from students even though there are no convincing evidence to prove that PBL does in fact increase students' performance.